О положении и статусе Сугдеи в VI—IX вв. - Сорочан, С.Б. (My University, 2008)
S. Sorochan. About situation and status of Sugdeja in VI—IX centuries In the article are investigated all facts of written and archaelolgical sources which concern to presence in Sugdeja the authorities of Byzantium and Khazars qaghanate. They do not allow to judge domination Khazar’s in city. It was not bulgarian, bat byzantian centre. From the end of VII centurie before the time of formation in Crimea the thema of Climate it had the condominium status of Byzantium and Khazar qaghanate.